Effects of intensive agriculture and climate change on biodiversity - Reyes Palomino, Smith Ervin (2022)
Biodiversity is being affected by the overexploitation of natural resources, the increase of invasive species, climate change, intensive agriculture, and livestock farming. Among these, intensive soybean cultivation has displaced other products such as rice and wheat; intensive cultivation leads to increased use of agrochemicals, which generates severe socio-environmental effects, particularly on biodiversity. The objective of the study was to compile scientific literature produced on the loss of biodiversity caused by intensive agriculture and climate change, and within them the possible effects on the interrelationship between human beings and the environment. The methodological procedure was the systematic review developed in March 2021, using Boolean operators AND, OR, NOT with terms “biodiversity”, “climate change” and “agriculture” in the Scopus, Web of Science and Scielo databases. The results identified that there were at least 99 topics in Web of Science (99 topics), Scopus (155 topics) and Scielo (36 topics) that show the loss of biodiversity due to climate change and the expansion of intensive agriculture with consequences, not only in the regions surrounding the crops in question, but also indirectly in the mountain regions through the consumption of soybean in animals and derivatives in humans. It is concluded that biodiversity as a provider of food and disease prevention for humanity contributes to sustainability and, therefore, its preservation requires the adoption of aggressive public policies within the framework of the Convention on Biological Diversity.